1991
DOI: 10.1042/bj2750697
|View full text |Cite
|
Sign up to set email alerts
|

Bovine adrenal chromaffin cells contain an inositol 1,4,5-trisphosphate-insensitive but caffeine-sensitive Ca2+ store that can be regulated by intraluminal free Ca2+

Abstract: We have characterized some properties of the caffeine-sensitive Ca2+ store in bovine chromaffin cells. Addition of 10 mM-caffeine to permeabilized cells that were allowed to sequester Ca2+ in the presence of the precipitating anion pyrophosphate induced a transient rise in free Ca2+ concentration that was blocked by 10 microM-Ruthenium Red. Caffeine was able to release Ca2+ after the InsP3-sensitive Ca2+ pool had been completely emptied, and 10 microM-InsP3 still released Ca2+ in the presence of a high dose (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…During the last few years evidence in favor of IP3-independent release mechanisms has indeed been accurnulated in various cell types [21,[31][32][33][34].…”
Section: I__/ Crmentioning
confidence: 99%
“…During the last few years evidence in favor of IP3-independent release mechanisms has indeed been accurnulated in various cell types [21,[31][32][33][34].…”
Section: I__/ Crmentioning
confidence: 99%
“…GTP-dependent release [6] and uptake [10] processes have been described in organelles that are distinct from those that affect Ins(1,4,5)PJ, and more recently a large number of studies have described Ca2l-induced Ca2+-release mechanisms (using caffeine as a pharmacological probe) from the Ins(1,4,5)P3-insensitive stores, and such mechanisms are thought to be important in the propagation of Ca2+ oscillations (e.g. [11][12][13][14]). In platelets the intracellular Ca2+ store has often been referred to as the dense tubular system [15,16] and is a membrane system that is analogous to the smooth sarcoplasmic reticulum of skeletal muscle.…”
mentioning
confidence: 99%
“…Poulsen et al (29) showed that the receptors for IP3 and ryanodine are co-distributed in subfractions of microsomes by immunoblotting using specific antibodies, which supports the results of the present study. On the other hand, Cheek et al (10), and Robinson and Burgoyne (11) reported that IP3 and caffeine released Ca2+ from discrete Ca2+ stores, while Stauderman et al…”
Section: Assays Of Protein and Organelle Markermentioning
confidence: 99%
“…On the other hand, caffeine, a powerful potentiator of Ca2+-induced Ca2+ release (CICR) from the sarcoplasmic reticulum in muscle, evoked Ca2+ mobilization and catecholamine secretion (4,6,7) in a Ca2+-free condition, and both were blocked by the CICR channel inhibitor ryanodine in an use-dependent manner in bovine adrenal chromaffin cells (5,8). Furthermore, using digitonin-permeabilized cells of the bovine adrenal medulla, IP3 was found to release Ca2+ from internal store sites (9), which was distinct from caffeine-sensitive stores (10,11). The results of these studies indicate the existence of functional Ca2+-storage sites, which are responsive to IP3 or caffeine in adrenal chromaffin cells (12).…”
mentioning
confidence: 98%